Pathology of Early Malignant Change in the Ovary: A short review article (Bangladesh Journal of Pathology, 2010)
Key words: Ovarian tumor-early malignant changeDOI: 10.3329/bjpath.v24i2.4114Bangladesh J Pathol 24(2): 21-24